Toward Return to Duty Decision-Making After Military Mild Traumatic Brain Injury: Preliminary Validation of the Charge of Quarters Duty Test. Issue 7 (28th June 2018) - Radomski, Mary V; Davidson, Leslie F; Smith, Laurel; Finkelstein, Marsha; Cecchini, Amy; Heaton, Kristin J; McCulloch, Karen; Scherer, Matthew; Weightman, Margaret M
Abstract: Introduction: Determining duty-readiness after mild traumatic brain injury (mTBI) remains a priority of the United States Department of Defense as warfighters in both deployed and non-deployed settings continue to sustain these injuries in relatively large numbers. Warfighters with mTBI may experience unresolved sensorimotor, emotional, cognitive sequelae including problems with executive functions, a category of higher order cognitive processes that enable people to regulate goal-directed behavior. Persistent mTBI sequelae interfere with warfighters' proficiency in performing military duties and signal the need for graded return to activity and possibly rehabilitative services. Although significant strides have been carried out in recent years to enhance the identification and management of mTBI in garrison (EXORD 165–13) and deployed settings (EXORD 242–11; DoDI 6, 490.11), the Department of Defense still lacks reliable, valid, and clinically feasible functional assessments to help inform duty-readiness decisions. Traditional functional assessments lack face validity for warfighters and may have ceiling effects, especially as related to executive functions. Performance-based multitasking assessments have been shown to be sensitive to executive dysfunction after acquired brain injury but no multitasking assessments have been validated in adults with mTBI. Existing multitasking assessments are not ecologically valid relative to military contexts. A multidisciplinary military–civilian team of researchers developed and evaluated a performance-based assessment called the Assessment of Military Multitasking Performance. One of the Assessment of Military Multitasking Performance multitasks, the Charge of Quarters Duty Test (CQDT), was designed to challenge the divided attention, foresight, and planning dimensions of executive functions. Here, we report on the preliminary validation results of the CQDT. Materials and Methods: The team conducted a measurement development study at Fort Bragg, NC, enrolling 83 service members (33 with mTBI and 50 healthy controls). Discriminant validity was evaluated by comparing differences in CQDT sub-scores of warfighters with mTBI and healthy controls. Associations between CQDT sub-scores and neurocognitive measures known to be sensitive to mTBI were examined to explore convergent validity. The study was approved by the Womack Army Medical Center Institutional Review Board (Fort Bragg). Results: There were significant between-group differences in two of the four CQDT sub-scores (number of visits, p = 0.012; and performance accuracy, p = 0.020). Correlations between the CQDT sub-scores and some neurocognitive measures were statistically significant but weak, ranging from 0.287 (CQDT performance accuracy and NAB Numbers and Letters, Part D) to −0.421 (CQDT total number of visits and Automated Neuropsychological Assessment Metrics Tower Task). There were group differences in terms of participants' reading level, education, years in military, and stress symptoms; some of these characteristics may have influenced CQDT performance. Conclusions: The CQDT demonstrated initial evidence of discriminant validity. Further study is warranted to more formally evaluate convergent/divergent validity and ultimately how and whether this performance-based multitasking measure can inform readiness to return to duty after mTBI.